2016
DOI: 10.1167/16.10.12
|View full text |Cite
|
Sign up to set email alerts
|

Not only amblyopic but also dominant eye in subjects with strabismus show increased saccadic latency

Abstract: Amblyopia is a developmental disorder of vision usually associated with the presence of strabismus and/or anisometropia during early childhood. Subject literature has shown that both the amblyopic and fellow eyes (especially in strabismic subjects) may manifest a variety of perceptual and oculomotor deficits. Previous studies using simple saccadic responses (pro-saccades) showed an increased saccadic latency only for the amblyopic eye viewing conditions. So far, there have appeared no saccadic latency studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
(93 reference statements)
1
21
0
Order By: Relevance
“…It is commonly known that saccadic reaction time in response to amblyopic eye stimulation is substantially increased as compared to the dominant eye or normal eyes (Ciuffreda, Kenyon, & Stark, 1978;Niechwiej-Szwedo et al, 2012;Perdziak et al, 2014;McKee et al, 2016;Perdziak et al, 2016). In the present study, we have also observed an increased saccadic latency for amblyopic eye viewing that is in agreement with previous research.…”
Section: Saccadic Latency In Amblyopiasupporting
confidence: 93%
See 1 more Smart Citation
“…It is commonly known that saccadic reaction time in response to amblyopic eye stimulation is substantially increased as compared to the dominant eye or normal eyes (Ciuffreda, Kenyon, & Stark, 1978;Niechwiej-Szwedo et al, 2012;Perdziak et al, 2014;McKee et al, 2016;Perdziak et al, 2016). In the present study, we have also observed an increased saccadic latency for amblyopic eye viewing that is in agreement with previous research.…”
Section: Saccadic Latency In Amblyopiasupporting
confidence: 93%
“…Several previous studies have shown that amblyopia may affect smooth pursuit, fixational eye movements, or fixation stability (Ciuffreda, Kenyon, & Stark, 1979;Gonzalez, Wong, Niechwiej-Szwedo, Tarita-Nistor, & Steinbach, 2012;Subramanian et al, 2013;Chung, Kumar, Li, R. & Levi, 2015;Ghasia, 2015;Shaikh, Otero-Millan, Kumar, & Ghasia, 2016;Kelly, Cheng-Patel, Jost, Wang, & Birch, 2018). In terms of saccadic eye movements, reduced precision of saccade amplitude or increased saccadic reaction time (latency) may be present in amblyopic subjects (Niechwiej-Szwedo, Chandrakumar, Goltz, & Wong, 2012;Perdziak, Witkowska, Gryncewicz, Przekoracka-Krawczyk, & Ober, 2014;McKee, Levi, Schor, & Movshon, 2016;Perdziak, Witkowska, Gryncewicz, & Ober, 2016). However, in the vast majority of previous research, saccadic latency in amblyopic subjects was measured during the classic paradigm in which the peripheral target is switched on simultaneously with an offset of fixation target-there is no gap condition.…”
Section: Introductionmentioning
confidence: 98%
“…This paper explored fellow eye deficits in five visual tasks that have been extensively studied in amblyopia. However, children and adults with amblyopia have demonstrated abnormalities in the fellow eye for a range of additional tasks not discussed here: for example, in foveal function, 294 pupillary response amplitudes, 295 fixational eye movement patterns, 296,297 smooth pursuit, 123 saccadic latency, 298 visual evoked potentials to both form and motion stimuli, 226,[299][300][301][302] blur discrimination, 303 global shape perception, 304 orientation adaptation, 305 line bisection, 306 the extraction of threedimensional structure, 307 maximum motion displacement thresholds, 308,309 single-object tracking, 40 multiple-object tracking, 40,41 scene perception, 310 perception of the McGurk effect, 311 and visual decision-making. 312 Many of these visual functions have been assessed during fellow eye viewing in only a handful of studies, so more work is needed to determine how robust these deficits are and the conditions under which they occur.…”
Section: Discussionmentioning
confidence: 99%
“…While amblyopic eyes show poorer fixation stability than control eyes during both monocular and binocular viewing, fellow eyes have fixation stability comparable to that of controls, both when fixating or under binocular viewing . However, the initiation of tracking pursuits is delayed and saccadic latency of the non‐amblyopic eye can be less accurate than in age‐matched controls …”
Section: Visual Deficits In Amblyopiamentioning
confidence: 99%